2012
DOI: 10.1177/0731684412448448
|View full text |Cite
|
Sign up to set email alerts
|

Using industrial waste of old corrugating containers paper recycling mill in composite panels manufacturing

Abstract: There is a considerable amount of waste produced daily from processing old corrugating containers. Dumping this waste product incurs a considerable cost to a paper recycling mill. In this study a sample of waste containing 45% fibrous and 55% non-fibrous solid was collected from an old corrugating containers paper-recycling mill and analyzed in a laboratory. The waste was used to produce wastes-urea formaldehyde composites and wastes-polyethylene composites. Physical and mechanical properties of the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A 5 cm wide edge of each board was trimmed to remove the low density and poor bonding areas of the boards (Younesi-Kordkheili et al. 2012). To ensure reproducibility, three panels were manufactured for each formulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 5 cm wide edge of each board was trimmed to remove the low density and poor bonding areas of the boards (Younesi-Kordkheili et al. 2012). To ensure reproducibility, three panels were manufactured for each formulation.…”
Section: Methodsmentioning
confidence: 99%
“…Pressing the compound material was carried out respectively in two stages by hot and cold presses for 5 min. A 5 cm wide edge of each board was trimmed to remove the low density and poor bonding areas of the boards (Younesi-Kordkheili et al 2012). To ensure reproducibility, three panels were manufactured for each formulation.…”
Section: Panel Manufacturingmentioning
confidence: 99%
“…In addition, according to the USA Environmental Protection Agency, recycling one ton of paper saves over 3.3 cubic yards of landfill space and 17 trees [277]. Recycling paper is also important for countries with scarce forests and hence need to promote conservation [278]. The benefits of recycling paper are not limited to the PPI alone.…”
Section: Recycling Pulp and Paper Productsmentioning
confidence: 99%
“…Used for recycling Technology, But of this trial The main purpose of the recycling paper mill is to determine the compatibility of OCC residue to produce composite panels. Literary criticism has suggested that the waste of OCC paper recycling plants may be a good alternative as a fortifying agent for compounds [28]. Water within the PCB and metal finishing industries Recycling and metal recovery.…”
Section: Powder Recyclingmentioning
confidence: 99%